2023
DOI: 10.1038/s41598-023-27965-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the protection of influenza virus vaccines with BECC TLR4 adjuvant in aged mice

Abstract: Influenza A virus (IAV) is a leading cause of respiratory disease worldwide often resulting in severe morbidity and mortality. We have previously shown that the Bacterial Enzymatic Combinatorial Chemistry (BECC) adjuvants, BECC438 and BECC470, formulated with an influenza virus hemagglutinin (HA) protein vaccine, offer greater protection from influenza virus challenge in mouse respiratory models using adult mice than standard HA:adjuvant combinations. In this study, we determined that immunization with HA + BE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…The lipid A modifications engineered in this study utilized the BECC approach whereby prior identification of lipid A modifying enzymes from a variety of Gram-negative bacteria then enabled the expression of select enzymes within a bacterium of interest. Previously, the BECC system has been employed to generate custom-designed lipid A molecules in Yersinia [50][51][52][53][54][55][56] ; however, this study extends its use to Shigella species, suggesting it is applicable to a variety of Gram-negative bacteria. More specifically, we showed that BECC enabled robust lipid A modification in both WT and vaccine strains of Shigella.…”
Section: Discussionmentioning
confidence: 98%
“…The lipid A modifications engineered in this study utilized the BECC approach whereby prior identification of lipid A modifying enzymes from a variety of Gram-negative bacteria then enabled the expression of select enzymes within a bacterium of interest. Previously, the BECC system has been employed to generate custom-designed lipid A molecules in Yersinia [50][51][52][53][54][55][56] ; however, this study extends its use to Shigella species, suggesting it is applicable to a variety of Gram-negative bacteria. More specifically, we showed that BECC enabled robust lipid A modification in both WT and vaccine strains of Shigella.…”
Section: Discussionmentioning
confidence: 98%
“…Future studies to more clearly define the immunostimulatory effects of BECC438b during vaccination against respiratory pathogens are warranted to better understand the data observed in this study. BECC technology used as adjuvants in vaccines against respiratory diseases like influenza has been explored previously with great success ( 95 , 96 ). While these applications did not explore route of administration, we believe our data prepare a case for its efficacy in novel intranasal vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, commensal bacteria are known to play a role in shaping the immune system tone, which may also influence vaccine efficacy (51). Recently, a study observed that potentiation of the innate immune response through Toll Like Receptor (TLR)-4 could enhance vaccine protection against influenza viruses in senescent mice (52). Given that SDP In conclusion, in this study, we have established a model of nasal immunization in senescent mice that protected them mucosally and systemically, as reflected by increased levels of anti-SEB-specific Igs and a higher survival rate to lethal shock with SEB.…”
Section: Discussionmentioning
confidence: 99%